Blue light induces leaf color change by modulating carotenoid metabolites in orange-head Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Rui-xing ZHANG; Ni-nan ZHANG; Ya-xiu WANG; ABID Khan; Shuai MA; Xue BAI; Qi ZENG; Qi-ming PAN; Bao-hua LI; Lu-gang ZHANG (Journal of Integrative Agriculture, 2023)
Carotenoids are involved in the formation of plant leaf color as well as photosystem photoprotection. This study showed that blue light significantly induced up-regulation of the total carotenoid content in the inner leaves of orange-head Chinese cabbage (OHCC). Furthermore, the transcriptomic analysis revealed that blue light treatment induced up-regulation of genes in photosynthesis (BrHY5-2, BrCOP1 and BrDET1) and the methylerythritol 4-phosphate pathways (BrGGPS, BrDXS and BrHDR) upstream of the carotenoid metabolic pathway. Carotenoid metabolomic analysis revealed that the accumulation of several orange and red carotenoids (lycopene, zeaxanthin, β-carotene, lutein, and β-cryptoxanthin) after blue light treatment contributed to the deepening of the leaf coloration, suggesting that short-term blue light treatment could be used to boost nutritional quality. The light signal gene BrHY5-2 participated in the blue light-induced transcriptional regulation of carotenoid biosynthesis in OHCC. Overexpression of BrHY5-2 in Arabidopsis significantly increased the total carotenoid content and the sensitivity to blue light. The above findings revealed new insights about blue-light-induced carotenoid synthesis and accumulation in OHCC lines. They suggested a new engineering approach to increase the nutritional value of vegetables.